Changes in the Livelihood Environment of Fishermen in Tambak Lorok Village - Nur Inayah Syaharani (Jurnal Masyarakat Maritim, 2025)
This study explores the changes in the livelihood environment of fishermen in Tambak Lorok Village, a coastal community that has faced significant ecological, social, and economic transformations over the past decade. The research aims to analyze how environmental degradation, coastal reclamation, and climate change have affected fishermen’s sources of income, social structure, and adaptive capacity. Using a qualitative descriptive approach, data were collected through interviews, participatory observation, and documentation involving local fishermen, community leaders, and related institutions. The findings reveal that shifts in marine ecosystems, reduced fish populations, and coastal pollution have directly disrupted traditional fishing patterns and decreased household income levels. In response, fishermen have adopted various adaptive strategies, including diversification of livelihoods through fish trading, aquaculture, and informal labor in nearby urban areas. Social networks and community solidarity continue to play a vital role in sustaining economic and emotional resilience, as reflected in cooperative activities and local support systems. However, limited access to capital, declining environmental quality, and inadequate policy support remain significant challenges. The study concludes that the livelihood transition among Tambak Lorok fishermen represents a dynamic interaction between environmental change and human adaptation. Strengthening sustainable coastal management, providing economic diversification programs, and integrating local participation into development planning are essential to ensure long-term resilience and livelihood security in coastal communities affected by environmental transformation